2011
DOI: 10.4025/actascianimsci.v33i3.9462
|View full text |Cite
|
Sign up to set email alerts
|

Cinética da fermentação in vitro do capim-Marandu em diferentes idades de corte

Abstract: RESUMO. O objetivo do trabalho foi avaliar os parâmetros da cinética de degradação ruminal da Brachiaria brizantha cv. Marandu, cortadas aos 28, 35 e 54 dias, pela técnica in vitro de produção de gases. Foram realizadas determinações dos teores de matéria seca (MS), matéria orgânica (MO), proteína bruta (PB), extrato etéreo (EE), fibra em detergente neutro corrigida para cinzas e proteína (FDN CP) , fibra em detergente ácido (FDA), nitrogênio insolúvel em detergente neutro (NIDN), nitrogênio insolúvel em deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
1
6
2
2
Order By: Relevance
“…Each 1% of added starch promoted a linear increase in total gas production of 0.2254 ml and a decrease in lag time of 0.2451 h. Higher gas production occurred with greater nutrient availability (NFC) for rumen microorganisms in vitro (WASCHECK et al, 2010) as the added starch replaced the forage, which has a high NDF. Similar results were found by Sá et al (2011), where the higher NFC amount of marandu palisadegrass promoted higher in vitro gas production.…”
Section: Resultssupporting
confidence: 78%
“…Each 1% of added starch promoted a linear increase in total gas production of 0.2254 ml and a decrease in lag time of 0.2451 h. Higher gas production occurred with greater nutrient availability (NFC) for rumen microorganisms in vitro (WASCHECK et al, 2010) as the added starch replaced the forage, which has a high NDF. Similar results were found by Sá et al (2011), where the higher NFC amount of marandu palisadegrass promoted higher in vitro gas production.…”
Section: Resultssupporting
confidence: 78%
“…In addition, a high "a" fraction rate in these leguminous plants can show the presence of higher amounts of soluble carbohydrates such as starch and monosaccharides, which are present in plant cells. Notably, the soluble "a" fraction can contribute to ruminal synthesis of volatile fatty acids, considered the main source of energy for ruminants (SÁ et al, 2011). Stylosanthes aged 55 days presented a lower soluble "a" fraction than the other studied plants (13.26%).…”
Section: Resultsmentioning
confidence: 86%
“…Evangelista et al (2002) studied the in situ degradability of 15 alfalfa cultivars, and found similar mean values for fraction B (38.0 to 44.4%) and higher for kd rate (0.078 to 0.124/h) and potential degradation (78.4 to 81.6%). Veloso et al (2006) Sá et al (2011) for Brachiaria brizantha (12.9 to 14.6 h), with ages ranging from 28 to 54 days, and by Campos et al (2000) for corn silage (6.2 to 9.1 h) in a period of 48 hours. The fiber fraction is directly related to most of the events involved in this parameter.…”
Section: Resultsmentioning
confidence: 99%